(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Great new technologies have been contributed by Information technology industries to the world. The introduction of new technologies affects psychosocial and mental health of professionals working in this industry. This study tries to understand stressors in occupation of sixty-one leads and sixty-two team members working in IT industry in Bangalore. Managers and team members are metered using (Occupation Stressor Indicator) OSI index.It was understood that inner elements of job like Type A behavior, Organizational forms and atmosphere were callers for mental disorders and physical ill health in managers. Studies guided statistically that Organizational forms and atmosphere and relationship with people were key callers in team members. Management operations and organizational strengths were main reasons for job satisfaction for both the groups. It is brought out that these outcomes mirror huge economic and communal changes taking place in the industry in Bangalore.